1993
DOI: 10.1089/aid.1993.9.529
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Two Primary Human Immunodeficiency Virus Type 1 Isolates to Growth in Transformed T Cell Lines Correlates with Alterations in the Responses of Their Envelope Glycoproteins to Soluble CD4

Abstract: Two sCD4-resistant, primary viruses (P-08 and P-17) were compared with two sCD4-sensitive, T cell line-adapted variants (C-08 and C-17) for their biochemical responses to sCD4. At 37 degrees C, neither primary virus shed gp120 within 8 hr at sCD4 concentrations of up to 500 nM, whereas C-08 and C-17 lost gp120 within minutes of addition of 5-10 nM sCD4. At 4 degrees C, however, P-17 and C-17 shed gp120 at similar rates in response to the same sCD4 concentration. Irrespective of the temperature, gp120 dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
69
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 72 publications
18
69
1
Order By: Relevance
“…Primary HIV-1 isolates have proven to be relatively resistant to soluble CD4, probably due to the fact that these viruses have adapted to replicate in the presence of neutralizing antibodies to CD4BS, which are highly prevalent in patient sera (3,12,23,37,57,58,60,63,65,86). HIV-1 cultured in the absence of neutralizing antibodies in vitro rapidly adapts, and more-neutralization-sensitive variants emerge (6,56,57,70,100). This change in phenotype has been attributed to an alternate interaction with CD4, potentially generating a greater affinity of the envelope for CD4 while simultaneously exposing neutralization epitopes, particularly those associated with the CD4 binding site (70).…”
Section: Resultsmentioning
confidence: 99%
“…Primary HIV-1 isolates have proven to be relatively resistant to soluble CD4, probably due to the fact that these viruses have adapted to replicate in the presence of neutralizing antibodies to CD4BS, which are highly prevalent in patient sera (3,12,23,37,57,58,60,63,65,86). HIV-1 cultured in the absence of neutralizing antibodies in vitro rapidly adapts, and more-neutralization-sensitive variants emerge (6,56,57,70,100). This change in phenotype has been attributed to an alternate interaction with CD4, potentially generating a greater affinity of the envelope for CD4 while simultaneously exposing neutralization epitopes, particularly those associated with the CD4 binding site (70).…”
Section: Resultsmentioning
confidence: 99%
“…Early observations revealed that tissue culture-adapted viruses, in the absence of antibody selection, result in the premature exposure of CD4-induced epitopes (88)(89)(90)(91), indicating that the Env protein for these viruses is in a more open conformation that exposes the coreceptor binding site. Furthermore, studies have shown that tissue culture-adapted viruses evolved to use low CD4 for entry (92,93) were more sensitive to sCD4 (94)(95)(96) and had greater sensitivity to antibody neutralization than typical primary isolates (58,89,92,97). Together, these observations raised the possibility that these phenotypes covary and are generated by the same mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two of the selected substitutions, I595F and K655E, were situated at the gp41 region. It is interesting to note that the same I595 residue has been implicated in the development of sCD4 sensitivity (38). The reasons why these gp41 substitutions were selected by BMS-378806 and the impact these changes have on envelope conformation await further studies.…”
Section: Discussionmentioning
confidence: 99%